The Remains of Megalithic Culture of Banyuwangi in East Java and The Historical Interpretation as Teaching Materials for Local History Learning - Kayan Swastika; Sumarjono Sumarjono; Mohamad Na’im; A. Ryan Pratama (Pancaran Pendidikan, 2021)
This research aims to: 1) describe the facts regarding the number and distribution pattern of archaeological remains of megalithic culture in Banyuwangi; 2) elaborate typology and identification of functions associated with the archaeological remains 3) reconstruct the conception of belief; 4) reconstruct social and economic life; 5) reveal the characters of megalithic culture in Banyuwangi and their relation to megalithic culture in Iyang-Ijenhighlands. The research was designed as historical research. The results of the study draw the following conclusion: 1) forty-six archaeological remains of megalithic culture are found in 13 sites spread over 10 districts in Bayuwangi; 2) the typology of remains consists of (a) stone platform, (b) stone of worship, (c) menhir, (d) series of TemuGelangBatu, (e) stone terraces, (f) monoliths, and (g) lumpangstone; 3) ancestor worship; 4 economic life already has a fairly complex and sufficient economic order; 5)there is no significant difference in the megalithic culture in Banyuwangi compared to the megalithic culture in Iyang-Ijen Plateau.